Sosialisasi Pencegahan Kenakalan Remaja melalui Optimalisasi Ekstrakulikuler sebagai Wadah Pengembangan Karakter dan Masa Depan Menuju Indonesia Emas 2045 - Angga Rosidin; Jaka Maulana; Siska Marlina; Erlina Apsari Putri; Dina Awalia; Ash Shifatuz Zuhroh; Ade Alfiyah Suliawati; Tegar Trihadi (P3M FIA UNKRIS, 2025)
The prevention of juvenile delinquency is a crucial issue in efforts to build a healthy, productive, and character-driven generation. One effective approach is optimizing extracurricular activities as a platform for youth character development. Extracurricular activities not only develop students’ talents and interests, but also shape their positive attitudes, behaviors, and values. Through these activities, adolescents can be guided to enhance social skills, empathy, and emotional intelligence, which are essential in preventing delinquent behavior. This study aims to analyze the role of extracurricular activities in preventing juvenile delinquency and developing student character in the context of achieving Golden Indonesia 2045. Employing an empirical and systematic approach, the research explores various types of extracurricular activities that contribute to reducing the potential for delinquency, while also identifying the link between character development and adolescents' readiness to face future challenges. The study also emphasizes the importance of collaboration among schools, parents, and communities in creating an environment that fosters positive character development. The findings indicate that well-structured extracurricular programs can significantly reduce juvenile delinquency rates by enhancing self-awareness, social competencies, and personal responsibility. Furthermore, programs that incorporate national and moral values help strengthen youth readiness to face the challenges of Indonesia Emas 2045. Therefore, optimizing extracurricular activities can be a strategic effort to cultivate young individuals with strong character, integrity, and a readiness to contribute to national aspirations.